ANALISIS KEPATUHAN WAJIB PAJAK HOTEL BERDASARKAN PEMERIKSAAN PAJAK, SANKSI PERPAJAKAN, KONDISI KEUANGAN DAN PREFERENSI RESIKO PADA HOTEL-HOTEL YANG TERDAFTAR DI BAPPENDA KABUPATEN BOGOR - Setiawan, Ade Budi; Meliana, Siti (JURNAL AKUNIDA, 2017)
This research was aims to determine the influence of tax audit, tax penalties, financial condition and risk preference on tax compliance in paying taxes hotels at BAPPEDA (Revenue Service), Bogor. The population in this study are all registered taxpayer hotels in BAPPEDA (Revenue Service), Bogor .The sampling method used in this research is purposive sampling with criteria are accounting staff and tax professional of tax compliance in taxpayers hotels, who canât reach tax revenue targets during 2014-2015. The datas in this study was obtained by distributing questionnaires to 52 respondents on tax compliance in taxpayer hotels in Bogor City. This study was tested by using multiple linear regression analysis with SPSS 20.00 for windows. Based on the analysis result, it can be concluded that tax audit, tax penalties and financial condition had positive influence on tax compliance in taxpayer hotels at BAPPENDA (Revenue Service), Bogor. While risk preference, hasnât influence on tax compliance in taxpayer hotels at BAPPENDA (Revenue Service), Bogor.Keyword : Tax Audit, Tax Penalties, Financial Condition, Risk Preference, Tax Compliance, Hotels Taxpayer